School-Based Education on Prevention of Smoking Behavior in Adolescents - Mohammad Fuad; Andi Tenri Awaru; Muhammad Rachmat; Sitti Nailah Rustam; Eka Ernalifia Saputri; Wahyuni Hasan; Imanuelle Tamara Audrey Siampa; Farikha Aulia; Nildawati; Suriah (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2022)
This school-based education program for adolescents in Bontokassi was performed due to the high frequency of active adolescent smokers in this village. Who performed the education activity by giving counseling through lectures, movie demonstrations, group discussions, and question and answer sessions. The intervention was performed in SMPN 3 Galesong Selatan and SMAN 13 Takalar, involving 26 and 17 participants. The participants were given an evaluation sheet for pre and post-test to examine their knowledge and attitude changes after the intervention and increased knowledge score for SMPN 3 students from 6.29 to 12.53. Meanwhile, for SMAN 13 students, there was an increased score from 12.18 to 16.06. Similar to the knowledge score, there was an increase in attitude scores post counseling for SMPN 3 and SMAN 13 students (from 5.00 to 5.85 and from 5.12 to 5.88, respectively). It is concluded that school-based intervention to prevent and control smoking behavior among adolescents is needed.